Report of a curricular internship at a full service CRO - Vicente, Margarida Isabel de Sousa (2015)
The present report outlines the activities developed and the acquired experience during the curricular internship at DATAMEDICA, Serviços e Consultoria em Bioestatística, Lda., under the scope of the Pharmaceutical Biomedicine Master Course. The internship, which took place between September 2014 and April 2015, allowed the performance of several activities related to Clinical Research, namely preparation of clinical studies submissions to Competent Authorities; monitoring activities; medical writing and data management. The work developed during this internship was essential both to acquire an important basis regarding new professional, personal and social skills and to develop old ones face to Clinical Research and its most relevant stakeholders, such as communication, concentration, sense of responsibility, organisation and correct response in stressful situations. The internship also allowed me to contact with the daily life activities of a Full Service Clinical Research Organisation (CRO) and put into practice the knowledge acquired at the University.